O papel da agência nacional de telecomunicações na promoção das inovações no setor de telecomunicações brasileiro - Santos, Bruno Oliveira dos (2013)
Technological development is an essential aspect for internationally competitiveness of companies and countries. In this sense, the telecommunications industry is as essential part in this process, as it is known, in the conventional literature, as intrinsically linked and dependent on technological innovations. Thus, this study aims to investigate the importance of telecommunications, from the definition of innovation by neoschumpeterian approach, the role of the Brazilian regulatory agency, the National Telecommunications Agency ‒ ANATEL ‒ in promoting and stimulating investment and innovation in the telecommunications sector. For this purpose, this study intends to introduce the direct policies executed by the agency and a brief analysis of the regulatory apparatus adopted and its influence in stimulating innovation. Finally, we will present a analysis of the investments on innovative activities and the nature of this expenditure, through the analysis of data provided by the Survey of Innovation ‒ PINTEC. The preliminary results of this study highlight the poor performance of ANATEL in stimulating innovation in this sector, and especially the limited and restricted mark of innovative activities, which are summed up, in large part, for the adaptation of products to the Brazilian market